Utilization of HVS Paper Waste for The Manufacture of Oxalic Acid - Agung Subyakto; Fiqrotul Wasiyah; Linaniyyatul Masruroh (IPTEK The Journal of Engineering, 2021)
The purpose of this research is to determine the effect of time and temperature on the manufacture of oxalic acid from HVS paper waste by removing ink and alkali melting methods The research methodology began with the first stage, namely pre-treatment and then paper hydrolysis, weighing 600 grams of HVS paper waste. The HVS paper waste was put into a three-neck flask and 200 mL of 40% NaOH was added. The tools are assembled and set the time and temperature used. The time used is 60 minutes at a temperature of 55°C, 65°C, 75°C and 95°C, then a three-neck flask is heated. After heating is complete the solution is cooled. The filtrate was filtered into a 500 mL beaker glass then the remaining sediment was washed with hot aquadest into a beaker containing up to 400 mL of filtrate. The procedure was repeated for variations in time of 70, 80 and 90 minutes at temperatures of 55°C, 65°C, 75°C and 95°C, respectively. The second stage is crystallization of oxalic acid, pipette of the filtrate as much as 25 mL obtained from the hydrolysis results then added 10% CaCl2 to form a white precipitate of calcium oxalate. The precipitate was filtered then added 100 mL of H2SO4 4N so that the precipitate would break down into oxalic acid and calcium sulfate, then filtered and washed the remaining sediment using 96% ethanol. The filtrate is heated to a temperature of 70°C. The filtrate is cooled in ice water for about 24 hours to form oxalic acid crystals in the form of white needle crystals. The third stage is the calculation of the weight of oxalic acid (gr). The fourth stage is testing for oxalic acid using permanganate titration. Oxalic acid crystals were weighed as much as 0.3 grams then added 10 mL of distilled water and put into 250 mL Erlenmeyer, added 10 mL of H2SO4 4N. The solution is heated to a temperature of 60-70°C. In a hot state, the solution is titrated with 0.1 N potassium permanganate until the solution appears a pink color that does not disappear for 30 seconds. The fifth stage is the calculation of the yield (yield) of oxalic acid. The sixth stage is the melting test. The time and temperature in producing oxalic acid from the graph can be seen that the average temperature that produces the most oxalic acid is at 80 minutes and 65°C, which is 3.9 grams. The analysis results show that the melting point obtained is between 100-101 ° C. This happens because the oxalic acid in the research indicates that the oxalic acid corresponds to the actual melting point of oxalic acid based on the Indonesian National Standard (SNI), namely 101-102°C.